Impact of the Business Structure on Solvency of Property-Liability Insurance Companies and Its Mediating Effect - Shuang Wu; Yi Li (Discrete Dynamics in Nature and Society)
It is an important objective for insurers to optimize their business structures to prevent business risks. This paper examines the solvency risk management in property-liability insurance companies from the perspective of business structure optimization. We construct a logical framework to explain the impact of the business structure on solvency through profitability and reinsurance behavior of property-liability insurance companies. By constructing a mediating effect model, we tested 35 Chinese-funded property-liability insurance companies and 18 foreign-funded property-liability insurance companies in China’s insurance market from 2009 to 2015. Two major results were found as follows: first, the impact of the business structure on solvency is positively significant in small Chinese-funded insurance companies as well as foreign-funded insurance companies, while it is insignificant in large Chinese-funded insurance companies. Second, the mediating effect test shows that the intermediary channel of profitability does not exist, while the intermediary channel of reinsurance exists, and the reinsurance fully mediated the relationship between business structure and solvency only in foreign-funded insurance companies. Therefore, we suggest that small Chinese-funded insurance companies should actively develop nonauto insurance and improve the risk diversification effect of the diversified business structure. On the contrary, foreign-funded insurance companies should give play to their differentiated advantages and continue to concentrate on the operation of nonauto insurance in China’s insurance market. Besides, the above two types of companies should attach more importance to the positive role of reinsurance in solvency risk management in their business development strategies.